STUDY OF THE MEDICINE QUERCETINE EFFICIENCY IN COMPLEX TREATVENT OF PATIENTS WITH IRON DEFICIENCY ANEMIA - Borysenko, Dmytro; Vydyborets, Stanislav (SWorld-Ger Conference proceedings, 2023)
According to WHO/UNESCO, iron deficiency anemia (IDA) is a fairly common disease among the population of all countries. IDA - are a medical and socio-economic problem, since they affect children, adolescents, women of reproductive age, pregnant women and